Linguistic Practice across Virtual Space The Arab Identity Crisis - Smechi, WIDAD; GUEDJALI, AMINA (Milev Journal of Research and Studies, 2019)
Language is the component of civilization and human history, as well as the basis of culture on the one hand and identity on the other. Today, the Arab world has been invaded by electronics and the extreme popularity of the use of the Internet, especially by young people who have found their way through the virtual world, which is characterized by the fusion of languages ​​and dialects in the expression of events or even in self-expression. Users of communication technologies must therefore find a simple language or language that is compatible with the characteristics of this new world and the nature of dialogue, through its electronic media. This allows for the emergence of so-called hybrid language that employs words that combine two languages or Arabic words written in Latin letters or numbers. This has shown several problems that are evident in all areas of our lives.